Is the Pandemic Personal or Political? The Influence of Demographics and Risk Proximity on Attitudes toward COVID-19 Policy in Washington State. (July 2021) - Janning, Michelle; Cordner, Alissa; Galant-LaPorte, Zidane; Rosenberg, Lucy
Many social factors affect the extent to which people may support governmental policies aimed at mitigating risk. The authors ask how demographic variables, preexisting vulnerability, and proximity to health, economic, and care work impacts may shape attitudes about governmental policies aimed at risk reduction during the coronavirus disease 2019 (COVID-19) pandemic. Grounding their analysis in literature on risk perception and attitudes about health policy, the authors report results from survey research on COVID-19 among more than 2, 000 Washington State residents from summer 2020. Multivariate analyses show that proximity to the economic impacts of COVID-19 had little effect on policy support or trust, whereas proximity to health risk and care work impacts had moderate effect. Political orientation emerged as the strongest predictor of policy support, with conservatives showing less support than liberals for state health policies aimed at mitigating health risks associated with COVID-19.